1987
DOI: 10.1007/bf02535541
|View full text |Cite
|
Sign up to set email alerts
|

A metabolite of an antineoplastic ether phospholipid may inhibit transmembrane signalling via protein kinase C

Abstract: In our search for the mechanisms by which the drug 1-O-alkyl-2-O-methylglycero-3-phosphocholine (AMG-PC) inhibits tumor growth and metastasis, we have detected a metabolite, 1-O-alkyl-2-O-methylglycerol (AMG), in membranes of MO4 mouse fibrosarcoma cells grown in the presence of the drug. Synthetic AMG inhibited the activation of highly purified human protein kinase C by diacylglycerol in the presence of phosphatidylserine. Furthermore, AMG also inhibited the receptor-specific binding of 3H-phorbol-12,13-dibut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 16 publications
7
59
0
Order By: Relevance
“…It will now be of interest to verify the proposed role of PKC in these processes. The approach reported here may provide a novel tool to study the involvement of PKC in cellular processes, in addition to more conventional approaches like PKC down-regulation by long-term pretreatment with phorbol ester 1271 and the use of specific inhibitors such as staurosporin [28] and 1 -O-alkyl-2-0-methylglycerol [29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It will now be of interest to verify the proposed role of PKC in these processes. The approach reported here may provide a novel tool to study the involvement of PKC in cellular processes, in addition to more conventional approaches like PKC down-regulation by long-term pretreatment with phorbol ester 1271 and the use of specific inhibitors such as staurosporin [28] and 1 -O-alkyl-2-0-methylglycerol [29].…”
Section: Resultsmentioning
confidence: 99%
“…Examination of the amino acid sequence of PKC revealed that the regulatory domain of the enzyme contains a sequence (residues [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]) that fulfills most of the requirements for a PKC phosphorylation site. It contains a number of basic amino acid residues [9], but with an alanine residue instead of the phosphate acceptor serine.…”
Section: Methodsmentioning
confidence: 99%
“…The inhibition was described as competitively with respect to PS and to the activation by diacylglyerol or TPA. The lack of inhibitory action of ET-18-0CH3 on PK-C activity when added as separate liposomes (method (iii)) is remarkable and might explain the findings of Van Blitterswijk et al [20] who found no inhibition of PK-C by the ether lipid when added as separate liposomes. Even more striking is the effect of ET-I8-0CH3 when incorporated in the PS and diolein liposomes (method (ii)).…”
Section: Febs Lettersmentioning
confidence: 86%
“…unpublished results), obtained after affinity column chromatochraphy on immobilized PS [22]. 1"o investlgate tl~.c po~;sibility whether PKC could itself phosphorylatc tlle physiological activator, DG, the separation of the two activities was the original aim, Upon homogenization of WBC, 90e/o of the DG kinase activity was recovered in the cytosol fraction, whick displayed a 2-fold higher specific activity than the microsomal fraction.…”
Section: I Purification and Churacterization Of Dg Kimtse From Humentioning
confidence: 99%
“…1). These fractions were devoid of PKC activity (measured as descibed in [22]). In a similar rnanner, DG kinase was also purified from pig brain cytosol (results not shown).…”
Section: I Purification and Churacterization Of Dg Kimtse From Humentioning
confidence: 99%